Особливості розвитку української літератури в 20–30-х роках ХХ століття - Ануфрієв, В. В. (ХНУРЕ, 2020)
This article describes the events that influenced Ukrainian literature of the 20-30s of the XX century and about the main authors of that time.
Keywords: культурне розмаїття; українознавство; традиції; культура